Determinants of mass participation in community-based forest management in South-western Nigeria (2010)
In Nigeria forest management is faced with increasingly complex challenges of reconciling the demands of various stakeholders. The new designated global role of the forests (conservation, biodiversity, producer of wood, carbon sequestration and aesthetics) is also posing fundamental conflicts between the state forestry services and the local communities. This paper analyses the views of various stakeholders against their demographic and socio-economic background with the view of determining mass participation in the management of community forests in south-western Nigeria. Purposive and random sampling techniques were used to select Lagos, Osun, Ondo and Ogun states for the study. The target population for the study comprised the local inhabitants and other categories of people such as artisans, civil servant, teacher traders, living in enclaves and settlements around the forest reserves in the study area. Data was collected using 3 different sets of questionnaire with test-retest reliability value of 0.85. Focus Group Discussions (FGDs), was also used to elicit information on perceptions about income, household size, various management issues, indigenous knowledge, cultural values and views about other forestry stakeholders. Data generated were analyzed using descriptive and Logit Regression statistics. The study revealed that determinant of mass participation in community forests (CF) or community based forest management (CBFM) are resource oriented, user or community dependent, forestry agency specific, programme related, and environment/forestry system specific. It was also found that communities around and within the forest reserves were heterogeneous in nature. The heterogeneity of caste, class, ethnicity, assets, household size, and income in the co-unities sampled were important determinant of stakeholders' level of participation in forest management. Logistic Regression Analyses revealed that ethnicity, level of income, awareness of CF benefits will significantly determine the willingness of the local people to participate in CF or CBFM in South-western Nigeria. An improvement of respondents' awareness of CF, joint determination of benefits from CF and inclusion of forest user groups (FUG)views in forest management content will go a long way at positively impacting forest management in the study area.